Environmental health, climate change, and equity: Understanding geographic vulnerabilities - Gina Solomon; Matthew Gribble; Sheri Weiser (Field Actions Science Reports)
Although climate change is affecting the entire planet, local effects differ in both nature and severity according to geography. Some geographic differences are readily apparent – such as the inherent vulnerability of coastal areas to sea level rise – whereas others are emerging. Geographic vulnerabilities are modified by the built environment and by disparities in the ability to adapt to climate change, further complicating the risk across the globe. The complex interactions of climate threats, local geographic and social vulnerabilities, and adaptation can best be explored at the regional level through examples relevant to other regions facing similar issues. This article will describe general principles of geography and climate change risk and explore how these play out using four examples: harmful algal blooms in Alaska, loss of glaciers in Peru, sea level rise causing increased drinking water salinity in Bangladesh, and HIV and food insecurity in Kenya related to extreme weather. The magnitude of the threat to humans from climate change will be significant, and geographic vulnerability is in many ways immutable, but much can still be done by humans to either increase or reduce risk. Lessons from one region can inform strategies in areas across the globe that share similar geographic vulnerabilities.